A longitudinal study of bovine viral diarrhea virus in a semi-closed management dairy cattle herd, 2020–2022 - Al-Mubarak, Abdullah I. A.; Al-Kubati, Anwar A. G.; Skeikh, Abdullah; Hussen, Jamal; Kandeel, Mahmoud; Flemban, Baraa; Hemida, Maged Gomaa (Frontiers in Veterinary Science, 2023)
We conducted a longitudinal study in a semi-closed dairy cattle herd during the period from 2020 to 2022.Nasal swabs (n = 190), rectal swabs (n = 190), and sera (n = 190) were collected from 79 cows in this herd.Collected sera and swabs were tested using the commercially available ELISAs for the BVDV antibodies and antigens, respectively. Collected sera were also tested for the presence of BVDV nucleic acids using commercial real-time RT-PCR kits. Our data shows BVDV seroprevalence (18.8%, 15%, and 8.2%) in the tested animals in 2020-2022, respectively. None of the collected nasal swabs, rectal swabs, or sera tested positive for the BVDV antigen. Whereas 10.1%, 10%, and 18.1% of the tested sera were positive for the BVDV nucleic acid in 2020-2022, respectively. The incidence rate was estimated at 0.02446 new cases/year despite the detection of BVDV in seronegative animals on single or two occasions at ≥ 6-month intervals.Young calves and bulls remained apparently unexposed to BVDV despite their presence with BVDV-infected females, with no significant physical separation. Both seropositivity and nucleic acid detectability showed significant positive and negative correlations, respectively, with reproductive performance. Collectively, the present study provides useful clues about the transmissibility of BVDV in the presence of possibly persistently infected animals. To the best of our knowledge, this is the first longitudinal study of BVDV in the Eastern Region of Saudi Arabia. Further detailed characterization of the circulating BVDVs is encouraged.